From surrealism to less-exquisite cadavers : Léo Malet and the evolution of the French Roman Noir - Emanuel, Michelle (Faux Titre, 288., 2006)
Les nouveaux mystères de Paris (1954-1959), Léo Malet's fifteen-novel detective series inspired by Eugène Sue's nineteenth-century feuilleton, almost achieved the goal of setting a mystery in each of the twenty Parisian arrondissements, with Nestor Burma at the center of the action. In Burma, the "détective de choc" first introduced in 1943's 120 rue de la gare, Malet, considered the "father" of the French roman noir, creates a cultural hybrid, bringing literary references and surrealist techniques to a criminal milieu. Michelle Emanuel's groundbreaking study is particularly insightful in it.